Synthesis And Characterisation Of Carbon, Nitrogen Co-Doped-Titanium Dioxide/Sodium Alginate Buoyant Photocatalyst For Degradation Of Diazinon - Idris, Nurul Hidayah Mohamad (2024)
The utilisation of titanium dioxide (tio2)- based photocatalysts has garnered significant attention among researchers due to their promising potential for removing pollutants from wastewater. Buoyant photocatalysts are being explored as viable candidates for wastewater treatment applications, aiming to address filtration challenges during the treatment process. In this study, the design of modified tio2 with a highly durable buoyant carrier is essential to enhance its photocatalytic performance in degrading pollutants from wastewater. Subsequently, carbon (c) and nitrogen (n)-codoped tio2 nps with varying c:n percentages were successfully developed using the sol-gel method. These optimised c, n-tio2 nps exhibit favorable attributes, including activity in the visible light region with a lower bandgap energy of 2.94 ev compared to the 3.0 ev of the synthesised tio2 nps, as well as slower recombination of electron-hole pairs than the synthesised tio2 nps. X-ray photoelectron spectroscopy (xps) analysis further verified the co-doping of c and n into tio2, evidenced by the shift in ti2p binding energy.